Sovereignty as the Quintessence of National Values - Nanzaddorj, Jalbajav (Mongolian Journal of Strategic Studies, 2025)
No abstract in English Mongolian title: Тусгаар тогтнол: Улс үндэстний үнэт зүйлсийн охь болох нь